2016
DOI: 10.1155/2016/9805291
|View full text |Cite
|
Sign up to set email alerts
|

An Endomyocardial Biopsy of the Left Ventricle in an Anorexia Nervosa Patient with Sinus Bradycardia and Left Ventricular Systolic Dysfunction

Abstract: Anorexia nervosa (AN) is an eating disorder characterized by an abnormally low body weight, an intense fear of gaining weight, and a distorted perception of body weight. AN is a life-threatening condition that significantly increases the risk of death due to cardiac complications, such that at least one-third of all deaths in patients with AN are associated with cardiac causes including sudden death. In many reports, sudden death has been linked to reduced left ventricular function, structural changes, and QT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…1 Importantly, AN carries one of the highest mortality rates of any psychiatric illness, with a six-fold higher estimated death rate compared with age-matched peers. 5 In addition, patients with AN have been shown to have myocardial fibrosis, demonstrated by late gadolinium enhancement on cardiac magnetic resonance imaging, 6 endomyocardial biopsy, 7 and autopsy reports, 8 implicating a primary substrate for ventricular tachyarrhythmias. While AN is known to alter cardiovascular structure and function, and possibly cardiac repolarization, whether these abnormalities represent a mechanistic link to the high risk of sudden death in AN remains uncertain, primarily because definitive data on the occurrence of premorbid cardiac arrhythmias are sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Importantly, AN carries one of the highest mortality rates of any psychiatric illness, with a six-fold higher estimated death rate compared with age-matched peers. 5 In addition, patients with AN have been shown to have myocardial fibrosis, demonstrated by late gadolinium enhancement on cardiac magnetic resonance imaging, 6 endomyocardial biopsy, 7 and autopsy reports, 8 implicating a primary substrate for ventricular tachyarrhythmias. While AN is known to alter cardiovascular structure and function, and possibly cardiac repolarization, whether these abnormalities represent a mechanistic link to the high risk of sudden death in AN remains uncertain, primarily because definitive data on the occurrence of premorbid cardiac arrhythmias are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A number of cardiac structural abnormalities, including pericardial effusion and myocardial atrophy, are prevalent in patients with AN. 5 In addition, patients with AN have been shown to have myocardial fibrosis, demonstrated by late gadolinium enhancement on cardiac magnetic resonance imaging, 6 endomyocardial biopsy, 7 and autopsy reports, 8 implicating a primary substrate for ventricular tachyarrhythmias. However, the contribution of these structural abnormalities to the risk of sudden death in AN remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac abnormalities may involve the myocardium, the pericardium, the mitral valve and/or the heart related conduction system. Cardiac histological studies reported vacuolar degeneration, myocardium attenuation and moderate interstitial fibrosis, without inflammatory or necrosis features [10]. Clinical observations includes left ventricular dysfunction, cardiac hypotrophy, mitral valve prolapse, pericardial effusion [4,11] and QT long prolongation.…”
Section: Introductionmentioning
confidence: 99%